# How do you solve #(x-3)-2 = 6-2(x+1)#?

#{: (,(x-3)-2,=,6-2(x+1)), (rarr,x-5,=,6-2x-2), (rarr,x-5,=,4-2x), (rarr,3x,=,9), (rarr,x,=,3) :}#

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation (x-3)-2 = 6-2(x+1), first distribute the -2 on the left side and the -2 on the right side of the equation:

(x - 3) - 2 = 6 - 2(x + 1)

x - 3 - 2 = 6 - 2x - 2

Combine like terms:

x - 5 = 4 - 2x

Add 2x to both sides:

3x - 5 = 4

Add 5 to both sides:

3x = 9

Divide both sides by 3:

x = 3

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7